2000
DOI: 10.2224/sbp.2000.28.4.309
|View full text |Cite
|
Sign up to set email alerts
|

Self-Concept: The Generalizability of Research on the Sdq, Marsh/Shavelson Model and I/E Frame of Reference Model to United Arab Emirates Students

Abstract: In this study we examined the structure of self-concept (SC) and the internal/external (I/E) frame of reference model for elementary (n = 276) and junior high (n = 293) students in the United Arab Emirates. The results provided support for the multifaceted interpretation for both groups of students. However, the study provided stronger support for the hierarchical structure with junior high than with elementary students' data. Higher-order confirmatory factor analysis (HCFA) of each group revealed that the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
34
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 27 publications
(51 reference statements)
7
34
0
1
Order By: Relevance
“…Al though the BFLPE was statistically significant for both age cohorts in all the Islamic countries, it was significantly smaller-particu larly in the younger age cohort. In line with earlier research in Arab and Islamic countries ; see also Abu-Hilal & Bahri, 2000), we also found that relations between LI achieve ment and MSC were significantly smaller in the Islamic coun tries-again, particularly for the younger age cohort. These au thors previously speculated that students from these countries do not receive as much evaluative feedback about their achievement as Western and Asian students, and are not socialized in such a way as to critically evaluate their academic skills in relation to classmates.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Al though the BFLPE was statistically significant for both age cohorts in all the Islamic countries, it was significantly smaller-particu larly in the younger age cohort. In line with earlier research in Arab and Islamic countries ; see also Abu-Hilal & Bahri, 2000), we also found that relations between LI achieve ment and MSC were significantly smaller in the Islamic coun tries-again, particularly for the younger age cohort. These au thors previously speculated that students from these countries do not receive as much evaluative feedback about their achievement as Western and Asian students, and are not socialized in such a way as to critically evaluate their academic skills in relation to classmates.…”
Section: Discussionsupporting
confidence: 92%
“…These au thors previously speculated that students from these countries do not receive as much evaluative feedback about their achievement as Western and Asian students, and are not socialized in such a way as to critically evaluate their academic skills in relation to classmates. Indeed, consistent with speculations by Abu-Hilal and Bahri (2000) that self-concept formation of ASC and its relation with achievement in Middle Eastern Islamic middle school stu dents was similar to that found in younger students from Western countries, support for the BFLPE for eighth-grade Middle Eastern Islamic students is similar to that found for the fourth-grade cohort in the Western and Asian countries (for further discussion, see Abu-Hilal, 2001;Abu-Hilal & Aal-Hussain, 1997;Abu-Hilal & Bahri, 2000).…”
Section: Discussionsupporting
confidence: 84%
“…The I/E model has been widely used to examine data for students from different countries: Canada (Marsh et al, 1988), Germany (Mo¨ller & Ko¨ller, 2001), Hong Kong (Lee et al, 2000;, Norway (Skaalvik & Rankin, 1995), the United Arab Emirates (Abu-Hilal & Bahri, 2000), and the United States (Bong, 1998;Plucker & Stocking, 2001;Williams & Montgomery, 1995). Marsh and Hau (2004) also verified the I/ E model by investigating the PISA 2000 data across 26 countries.…”
Section: Educational Research and Evaluation 237mentioning
confidence: 95%
“…Moller and Koller (2004) reported results from 34 studies on the lIE model and found a weak mean correlation (d = .10, range = -.13 to .22) between mathematic and verbal academic selfconcepts. Besides academic self-concept, other variables have also been investigated with respect to their domain-specific organization, including self-efficacy, causal attributions, task values, and achievement goals (Abu-Hilal & Bahri, 2000;Bong, 1998;Bong & Skaalvik, 2003;Marsh, 1984Marsh, , 1986Moller & Koller, 200 I;Stevenson & Newman, 1986).…”
Section: Theoretical Assumptionsmentioning
confidence: 99%